Cognitive Impairment in Multiple Sclerosis Is Reflected by Increased Susceptibility to the Sound-Induced Flash Illusion - Yalachkov, Yavor; Bergmann, Heinrich Johannes; Soydaş, Dilara; Buschenlange, Christian; Fadai Motlagh, Laura Yasmine; Naumer, Marcus J.; Kaiser, Jochen; Frisch, Stefan; Behrens, Marion; Foerch, Christian; Gehrig, Johannes (Frontiers in Neurology, 2019)
Objective To determine whether the performance of multiple sclerosis (MS) patients in the sound-induced flash illusion (SiFi), a multisensory perceptual illusion, would reflect their cognitive impairment. Methods We performed the SiFi task as well as an extensive neuropsychological testing in 95 subjects (39 patients with relapse-remitting MS (RRMS), 16 subjects with progressive multiple sclerosis (PMS) and 40 healthy control subjects (HC)). Results MS patients reported more frequently the multisensory SiFi than HC. In contrast, there were no group differences in the control conditions. Essentially, patients with progressive type of MS continued to perceive the illusion at stimulus onset asynchronies (SOA) that were more than three times longer than the SOA at which the illusion was already disrupted for healthy controls. Furthermore, the number of failed tests in a broad neuropsychological battery encompassing measurements of working memory, attention, concentration, speed of information processing as well as general information processing ability was predicted in MS patients by their performance in the SiFi task for the longest SOA of 500 ms but not by age, years of education, vocabulary, depression or task-related changes in fatigue. Conclusions These findings support the notion that MS patients exhibit an altered multisensory perception in the SiFi task and that their susceptibility to the perceptual illusion is negatively correlated with their neuropsychological test performance. Thus, SiFi might be considered as a brief, non-expensive, language- and education-independent screening test for cognitive deficits in MS patients.